Evaluation of some biochemical markers in relation to COVID-19 mRNA vaccine - Fadhil, Meaad; Al-Azzawi, Buthainah (Journal of Biomedicine and Biochemistry, 2022)
Background The coronavirus disease 2019 (COVID-19) has become a national pandemic for more than 2 years, and it continues to have an unimaginable impact on our way of life and quality of life. It is critical to gain a  deeper understanding of how immunity is regulated in response to SARS-CoV-2 infection. The C-reactive.protein.(CRP) was the first acute phase protein to be identified, and it serves as a highly sensitive systemic indication of tissue damage, infection, as well as inflammation. Smooth muscle cells, lymphocytes, macrophages, endothelial cells, and adipocytes are all involved in the production of this protein. Interleukin.10.(IL-10), commonly described as human. cytokine.synthesis.inhibitory.factor (CSIF). The IL-10 gene in humans produces interleukin 10, a pleiotropic cytokine with strong anti-inflammatory as well as immunosuppressive activities.The Aim the aim of this study is to evaluate the vaccine effectiveness using diagnostic biochemical markers.Material and method this study included 125 patients (56 males and 69 females) with vaccinated and non-vaccinated COVID-19 with an age range of 20–70 years. These patients are divided into two main groups: 1. vaccinated (vaccinated with COVID-19 infection, vaccinated without COVID-19 disease, vaccinated recoveredfrom the CoV-19 virus), 2. Unvaccinated (infected with the CoV-19 virus and non-vaccinated, recovered from COVID-19 and unvaccinated). The outcome is measured using the enzyme-linked immunosorbent assay (ELISA) technique. This study was conducted during the period from November 2021 to May 2022 at Al-Shifaa medical center and the vaccine unit at Al-Diwaniyah Educational Hospital, Diwaniyah governorate, Iraq.Results The results showed an increase in CRP level for the vaccinated groups was significantly higher (P